Ionic liquid foam floatation coupled with ionic liquid dispersive liquid–liquid microextraction for the separation and determination of estrogens in water samples by high‐performance liquid chromatography with fluorescence detection. Issue 21 (23rd September 2014) - Zhang, Rui; Wang, Chuanliu; Yue, Qiaohong; Zhou, Tiecheng; Li, Na; Zhang, Hanqi; Hao, Xiaoke
<x xml:space="preserve">Abstract</x> An ionic liquid foam floatation coupled with ionic liquid dispersive liquid–liquid microextraction method was proposed for the extraction and concentration of 17‐α‐estradiol, 17‐β‐estradiol‐benzoate, and quinestrol in environmental water samples by high‐performance liquid chromatography with fluorescence detection. 1‐Hexyl‐3‐methylimidazolium tetrafluoroborate was applied as foaming agent in the foam flotation process and dispersive solvent in microextraction. The introduction of the ion‐pairing and salting‐out agent NH4PF6 was beneficial to the improvement of recoveries for the hydrophobic ionic liquid phase and analytes. Parameters of the proposed method including concentration of 1‐hexyl‐3‐methylimidazolium tetrafluoroborate, flow rate of carrier gas, floatation time, types and concentration of ionic liquids, salt concentration in samples, extraction time, and centrifugation time were evaluated. The recoveries were between 98 and 105% with relative standard deviations lower than 7% for lake water and well water samples. The isolation of the target compounds from the water was found to be efficient, and the enrichment factors ranged from 4445 to 4632. This developing method is free of volatile organic solvents compared with regular extraction. Based on the unique properties of ionic liquids, the application of foam floatation, and dispersive liquid–liquid microextraction was widened.